Spinal cord injury following thoracic and thoracoabdominal aortic repairs. (February 2015) - Panthee, Nirmal; Ono, Minoru
Objective: To discuss the currently available approaches to prevent spinal cord injury during thoracic and thoracoabdominal aortic repairs. Methods: We carried out a PubMed search up to 2013 using the Medical Subject Headings: "aortic aneurysm/surgery" and "spinal cord ischemia"; "aortic aneurysm, thoracic/surgery" and "spinal cord ischemia"; "aneurysm/surgery" and "spinal cord ischemia/cerebrospinal fluid"; "aortic aneurysm/surgery" and "paraplegia". All 190 original articles satisfying our inclusion criteria were analyzed for incidence, predictors, and other pertinent variables related to spinal cord injury, and we compared the results in recent publications with those in earlier reports. Results: The mean age of the 38, 491 patients was 65.3 ± 4.9 years. The overall incidence of paraplegia and/or paraparesis was 7.1% ± 6.1% (range 0%–32%). The incidence of spinal cord injury before 2000, from 2001 to 2007, and 2008–2013 was 9.0% ± 6.7%, 7.0% ± 6.1%, and 5.9% ± 5.2%, respectively ( p = 0.019). Various predictors of spinal cord injury were identified, extent of disease being the most common. Modification of surgical techniques, use of adjuncts, and better understanding of spinal cord perfusion physiology were attributed to the decrease in postoperative spinal cord injury in recent years. Conclusions: Spinal cord injury after thoracic and thoracoabdominal aortic repair poses a real challenge to cardiovascular surgeons. However, with evolving surgical strategies, identification of predictors, and use of various adjuncts over the years, the incidence of spinal cord injury after thoracic/thoracoabdominal aortic repair has declined. Embracing a multimodality approach offers a good insight into combating this grave complication.